PERANCANGAN ALAT KESEHATAN WIRELESS BODY AREA NETWORK MULTISENSOR BERBASIS APLIKASI ANDROID - Ihsan Mustaqiim; Ahmad Taqwa; Ade Silvia Handayani; Sopian Soim (Jurnal Qua Teknika, 2021)
In this study, we designed a multisensory medical device to carry out a process of monitoring body health that was integrated into the system so that the patient's health could be detected. This tool uses Wireless Body Area Network technology that can work with Android-based platforms in real time. In designing this tool, it is designed to detect body health automatically by displaying information about body temperature, blood pressure, heart rate and oxygen levels in the blood, then sending notifications to the server without wasting time, and recording physical health information data automatically. Real-time display on the smartphone, owned by the user and provides a readable body health status that is healthy, an indication or needs action.